From Values to Visits: Exploring the Economic Development Potential of Halal Tourism Through Islamic Destination Attributes - Nabila, Rifda; Bawono, Anton; Iffah, Zatul; Touray, Sally (Economica: Jurnal Ekonomi Islam, 2025)
There is a growing acknowledgment of Halal tourism as a strategic sector for economic development in Muslim-majority countries. This research investigates how Islamic destination features, including worship amenities, halal compliance, and overall Islamic values, influence travelers’ choices to halal destinations in Indonesia, moderated by tourism image. Using a quantitative method, this study analyzed data with structural equation modeling in SmartPLS 3, based on responses from 1,000 tourists visiting Indonesia’s ten leading halal destinations. The results indicate that all three Islamic attributes significantly influence the positions of a tourist attraction, while only worship facilities directly affect visiting decisions. Destination image itself plays a mediating role in shaping tourist behavior. These results underline the importance of integrating Islamic values into tourism development strategies to enhance destination competitiveness. The study provides practical insights for government officials, including the standardization of halal certification in tourism facilities, the provision of adequate worship infrastructures at leading destinations, and the integration of halal tourism into national and digital marketing strategies. These analytical procedures enhance Indonesia’s role as a worldwide frontrunner in halal tourism. The results further emphasize halal tourism’s capacity to drive continuous local economic growth grounded in cultural and religious values.